An Extended Cost-Effectiveness Analysis of Tobacco Price Increases in the Kyrgyz Republic - World Bank Group (World Bank, Washington, DC, 2018)
Globally more than 7 million deaths a year are attributed to tobacco use, approximately 10 percent of which are among nonsmokers exposed to secondhand smoke. Most of these deaths occur in low- and middle-income countries (LMICs), and among a relatively young population. If current smoking patterns continue, tobacco will kill about one billion people this century. Tobacco taxes are among the most cost-effective tobacco control measures in the world. Yet often countries are reluctant to raise tobacco taxes due to their perceived regressivity. This study simulates the impact of higher tobacco prices resulting from increases in tobacco excise tax in the Kyrgyz Republic. The study uses extended cost-effectiveness analysis to measure the distributional consequences of proposed excise tax increases on: (a) averted premature tobacco-related deaths; (b) averted out-of-pocket (OOP) expenditures on treating tobacco-related disease; (c) government savings resulting from averted treatment costs for those covered under the State Guaranteed Benefit Package; and (d) averted poverty cases as a result of OOP spending. The Kyrgyz Republic has already introduced gradual tobacco tax increases that will take place up to 2022, but steps should be taken to ensure that these increases result in real price increases and to strengthen other tobacco control measures such as ensuring access to cessation services.